CARACTERÍSTICAS MORFOLÓGICAS DO PELAME DE VACAS MESTIÇAS HOLANDÊS-GIR EM AMBIENTE TROPICAL (Veterinária Notícias, 2015)
CARACTERÍSTICAS MORFOLÓGICAS DO PELAME DE VACAS MESTIÇAS HOLANDÊS-GIR EM AMBIENTE TROPICAL